1994
DOI: 10.1051/jp2:1994184
|View full text |Cite
|
Sign up to set email alerts
|

Electro-optic effects of aqueous fd-virus suspensions at very low ionic strength

Abstract: The orientation in external electric fields of rod-like fd-virus particles (length ℓ= 895 nm, diameter d = 9 nm) in aqueous suspensions is examined by the electric birefringence method. In aqueous suspensions the negatively charged fd-particles are surrounded by a diffuse Debye cloud of counterions, which is characterized by the Debye-Hückel parameter κ. A special experimental set-up is used to vary the ionic strength of the suspension, i.e. the Debye-Hückel parameter, and therefore the electrostatic interpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 0 publications
2
47
1
Order By: Relevance
“…This complies with the negative birefringence found in Ref. [5]. As can be seen No birefringence is observed, which implies that this state is isotropic.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…This complies with the negative birefringence found in Ref. [5]. As can be seen No birefringence is observed, which implies that this state is isotropic.…”
supporting
confidence: 91%
“…A few experimental studies are reported on colloidal dispersions of rods at lower frequencies where interactions between polarized double-layers are important [5], [6]. In Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Anomalous alignment of fd-virus particles (very long and thin, stiff rods) perpendicular to the external field has been found in Ref. [1] at low frequencies (below 1 kHz) for fd-concentrations above the overlap concentration. The present authors observed field-induced phase/state transitions, dynamical states and non-equilibrium critical behaviour in concentrated fd-virus suspensions [2,3,4].…”
Section: Introductionmentioning
confidence: 69%
“…(1,2), the solution of the equation of motion (12) for the surface-charged density must satisfy the condition,…”
Section: The Model and Equations Of Motion For The Charge Density Andmentioning
confidence: 99%